Molecular and Clinical Insights in Malignant Brenner Tumor of the Testis With Liver Metastases:A Case Report - Parcesepe, Pietro; Coppola, Luigi; Remo, Andrea; D’Andrea, Mario Rosario; Coppola, Giulia; Simbolo, Michele; Manfrin, Erminia; Scarpa, Aldo; De Santis, Elena; Giordano, Guido (Frontiers in Oncology, 2021)
Malignant Brenner Tumor (mBT) is extremely rare. Although BT are almost exclusive ovarian neoplasms, they may constitute a highly unusual tumor of the testis; in fact, only seven fully documented cases have been reported to date. Because of their rarity, the pathogenesis of these tumors has not been clarified and there is no standard therapeutic approach. We report the first case of epididymal mBT with synchronous, multiple, liver metastases and a very dramatic clinical course. Both primary tumor and metastasis were subjected to mutational analysis of 20 cancer associated genes. Primary tumor showed FGFR3 Tyr375Cys and PIK3CA His1047Arg missense mutations. Both mutations are reported as pathogenic in ClinVar database. The same FGFR3 mutation was present in liver metastasis. Based on these results we believe that the FGFR pathway could be an ideal candidate for personalized treatment, offering hope to a subset of patients with mBT. Personalized approach, including mutational analysis and molecular testing should be required in patients with rare tumors in order to clarify diagnosis and improve therapeutic strategies.